A Novel Method for Deflection Calculation of Reinforced Concrete Stair Slabs considering Step Stiffness - Xiuzhong Peng; Chenhao Lu (Advances in Civil Engineering)
Stair slabs are some of the most common structural members with zigzag shapes in various buildings. However, the calculated deflection is usually overestimated during the design of stair slabs. In this article, the overestimated deflection is amended by utilizing step stiffness. To this end, it is assumed that the stress distribution of a unit cell in stair slabs is linear or bilinear under a constant bending moment. Stair slabs can be approximately regarded as flat slabs to derive the equivalent thickness based on the same bending strain energy. Subsequently, finite element (FE) models are established to verify that the obtained equivalent thickness can be applied to reinforced concrete (RC) stair slabs. To improve computational efficiency, the normalized models of stair slabs are adopted for further analysis. On this basis, a novel design method is proposed considering step stiffness for RC stair slabs. Furthermore, numerical examples are presented to compare the improved design method with the FE method and the conventional method. The results demonstrate that the design method considering step stiffness can not only ensure structural safety but also reduce concrete and steel consumption, making the design of stair slabs more economical and reasonable.